Euphorbia spellenbergiana (Euphorbiaceae), a new species from Mexico - Mayfield, Mark H.; Steinmann, Victor W. (Instituto de Ecología, A.C., 2010)
Euphorbia spellenbergiana is described and illustrated as a new species. It belongs to subgenus Chamaesyce within which it is easily distinguished from similar species by its possession of undivided styles with capitate stigmas. This new species is endemic to Mexico and occurs from central western Chihuahua to northern Michoacán. Although widespread, it is highly habitat-specific and prospers only in the moist soil around ephemeral pools in pine-oak forest, grassland and pachycaulous scrub at elevations from 2100 to 2600 m.